ACIDIC REMOVAL OF METALS FROM FLUIDIZED CATALYTIC CRACKING CATALYST WASTE ASSISTED BY ELECTROKINETIC TREATMENT - Valt,R. B. G. (2015)
AbstractOne of the main uses of catalysts in the oil industry is in the fluidized catalytic cracking process, which generates large quantities of waste material after use and regeneration cycles and that can be treated by the electrokinetic remediation technique, in which the contaminant metals are transported by migration. In this study, deactivated FCC catalyst was characterized before and after the electrokinetic remediation process to evaluate the amount of metal removed, and assess structural modifications, in order to indicate a possible use as an adsorbent material. The analyses included pH measurement and the concentration profile of vanadium ions along the reactor, X-ray microtomography, X-ray fluorescence, BET analysis and DTA analysis. The results indicated that 40% of the surface area of the material was recovered in relation to the disabled material, showing an increase in the available area for the adsorption. The remediation process removed nearly 31% of the vanadium and 72% of the P2O5 adhering to the surface of the catalyst, without causing structural or thermal stability changes.